High resolution comparative genomic hybridisation in clinical cytogenetics - Kirchhoff, Maria; Rose, Hanne; Lundsteen, Claes (Journal of medical genetics, 2001)
High resolution comparative genomic hybridisation (HR-CGH) is a diagnostic tool in our clinical cytogenetics laboratory. The present survey reports the results of 253 clinical cases in which 47 abnormalities were detected. Among 144 dysmorphic and mentally retarded subjects with a normal conventional karyotype, 15 (10%) had small deletions or duplications, of which 11 were interstitial. In addition, a case of mosaic trisomy 9 was detected. Among 25 dysmorphic and mentally retarded subjects carrying apparently balanced de novo translocations, four had deletions at translocation breakpoints and two had deletions elsewhere in the genome. Seventeen of 19 complex rearrangements were clarified by HR-CGH. A small supernumerary marker chromosome occurring with low frequency and the breakpoint of a mosaic r(18) case could not be clarified. Three of 19 other abnormalities could not be confirmed by HR-CGH. One was a Williams syndrome deletion and two were DiGeorge syndrome deletions, which were apparently below the resolution of HR-CGH. However, we were able to confirm Angelman and Prader-Willi syndrome deletions, which are about 3-5 Mb. We conclude that HR-CGH should be used for the evaluation of (1) dysmorphic and mentally retarded subjects where normal karyotyping has failed to show abnormalities, (2) dysmorphic and mentally retarded subjects carrying apparently balanced de novo translocations, (3) apparently balanced de novo translocations detected prenatally, and (4) for clarification of complex structural rearrangements.